Retrospective analysis of prescriptions for the treatment of cardiovascular diseases in the program «Affordable medicines» on the example of a pharmacy - V. S. Huz; O. M. Zaliska; N. M. Maksymovych (The State Expert Center of the Ministry of Health of Ukraine, 2020)
Improving access and affordability for patients of essential drugs in the treatment of cardiovascular diseases is a priority because mortality and a morbidity rates are high in Ukraine. In April 2017, the government launched the reimbursement program «Affordable medicines», which included drugs to treat cardiovascular disease. The aim of the study was a retrospective analysis of released prescriptions on the example of the pharmacy № 1 in Vynohradiv, Transcarpathian region, which serves patients from the city and Vynohradiv district, which allowed us to analyze and compare the structure of the appointments of primary care physicians and to identify the main INN, stocks of which should be a priority in pharmacies for the treatment of cardiovascular diseases. The objects of study were the records of the pharmacies about drugs released in the program for 24 months, the Orders of the Ministry of Health of Ukraine, the CMU Decisions, the Drug Registry for cardiovascular diseases, the cost for reimbursement in the program «Affordable Medicines» as well. Frequency analysis methods, ATC/DDD methodology, as well as methods of comparative, logical and content analysis were used. Data for the selected period were analyzed using frequency analysis methods and ATC/DDD method, and it was found that enalapril, spironolactone and clopidogrel were in the lead. It was found that the majority of patients in 2017 chose free drugs (more than 80%), and in 2018-2019 this rate was only 60%. According to prescriptions, about 92% are patients from Vynohradiv district, which confirms the improvement of access to drugs in the program «Affordable Medicines» for the rural population. The results were verified by comparing the released e-prescriptions for cardiovascular diseases in the city and district and found that the structure of prescriptions for cardiovascular diseases on e-prescriptions from April 2019 to April 2020 remains stable and the main share is 4 INN: clopidogrel, enalapril, amlodipine and bisoprolol. It is determined that in order for the «Affordable Medicines» program, the provision and convenience of patients, the pharmacies need to have an expanded list of trade names and a sufficient supply of enalapril, spironolactone, clopidogrel and bisoprolol.